Potential and availability of feed in paddy fields for sustainable livelihoods of moving duck farmers in Pinrang regency South Sulawesi province. Issue 1 (June 2021) - Kasim, K; Salman, D; Siregar, A R; Nadja, R A; Pakiding, W
Abstract: The purpose of this study was to determine the potential and availability of duck fodder in paddy fields that supports the sustainability of moving duck farmers' livelihoods. The research method used was measuring the type of food eaten by ducks in paddy fields after being harvested by tiling and cropping ducks. There were three types of local duck feed in paddy fields after harvesting that could be measured in this study, namely rice that was wasted and left behind on harvested stems (loses), golden snails and earthworms. The availability of feed based on dry weight, namely, paddy at 702.40 kg/hectare, golden snails at 251.20 kg/hectare and earthworms at 4 kg/hectare. The availability of feed in the form of golden snails was quite high, especially the fresh weight of 1.064 kg/hectare. Golden snails reproduced quickly when the fields were already inundated with water. The availability of feed in the form of earthworms is 40 kg/hectare. The results of the research from the harvesting of ducks released in the fields were the consumption of dry weight of feed of 53.24 g/duck. Thus, the estimated feed availability based on dry weight was 97.60 kg/hectare. So that one hectare of paddy fields could accommodate as many as 300 ducks for two months (60 days). For the sustainability of the availability of feed for ducks in the paddy fields after two months of grazing, it can be obtained from the fruit of paddy regrowth from paddy stalks/straw that live in paddy fields. Sources of food for ducks could also be obtained from grasses and small snails that have just hatched and several types of insects in the paddy fields. It concluded that the potential and availability of feed in the paddy fields after harvesting for ducks were still supportive. Therefore, it reduced the cost of feed for farmers.